Comparative Study of Growth Performance and Viability of Four Marine Fish Species under Cage Culture - Muya , Judith Wairimu; Manyala , Julius Otieno (African Journal of Education,Science and Technology (AJEST), 2015)
This study set out to investigate and compare the growth performance and viabilities of four different marine fish species for commercial cage culture. The study was carried out in Makongeni village along Kenya coast from April 2012 to November 2012 with four marine species: rabbit fish (Siganus vermiculatus Valenciennes, 1835), red snapper (Lutjanus argentimaculatus), milk fish (Chanoschanos) and groupers (Epinephelus fuscoguttatus). The experiment consisted of 16 floating cages, four cages for each species and each cage holding a total of 50 juvenile fish of weight between 50-70 gm, reared for six months. Monthly variations of mean weight for each species in each of the cages show that groupers had the highest final body weight (242 ± 10.2 g), whereas rabbit fish had the lowest final weight of 101 ± 3.63 g. One-way ANOVA showed that groupers mean weight differed significantly from the milk fish, red snapper and rabbit fish right from the second to the sixth month (F= 80.61; p<0.0001). The final mean length for each species also show that groupers had the highest final mean total length (26.1 ± 0.40 cm) follow by milk fish (24.1 ± 0.53 cm), rabbit fish (19.5 ± 0.52 cm) and lastly by red snapper (17.5 ± 0.22 cm. The variation in final mean length was significant between species (F= 82.35; p<0.0001). Percent Weight Gain (PWG) was 290.3% for groupers, 168.6% for milk fish, 125.6 for rabbit fish and 65.03% for red snapper. The initially high PWG of 57.1% declined to only 15.1% for grouper in the first month to only 15.1% in the fifth month. The Specific Growth Rate (SGR) was also highest for the grouper (0.89%) as compared to milkfish (0.65%), rabbit fish (0.53%) and red snapper (0.33%). The length weight relationship showed a positive allometric growth for milk fish (b=3.8; R2=0.800) and negative allometric growth for red snapper (b=1.7; R2=0.811), rabbit fish (b=2.8; R2=0.895) and the grouper (b=2.7; R2=0.966). The best Feed Conversion Ratio (FCR) was obtained in the grouper. Relatively poor FCR were obtained in all the four species with the highest value for the red snapper ((92.3 ± 8.35), rabbit fish (52.8 ± 11.2), milk fish (38.9 ± 2.68) and grouper (20.4 ± 1.99). The grouper had low mortality and high survival (98%) as compared to milk fish (81%), snapper (91%) and rabbit fish (93.5%). On economic viability, groupers were found to be more viable compared to other three since they had higher market value per piece of KSh. 40 as compared to KShs. 20 for the red snapper, KSh. 22 for rabbit fish and KShs. 25 for milk fish. Based on the results of growth rate, feed conversion ratio, survival and economic viability, it is concluded that groupers is the best candidate for culture as compared to the other three test species. It is recommended that intensive pilot culture of groupers be undertaken in cages to develop an enterprise budget and business plan for commercial investment to improve livelihoods of the coastal community and at the same time, open up the opportunities for further research on nutrition, husbandry and further research on growth requirement of groupers.